2003
DOI: 10.1002/jmor.10142
|View full text |Cite
|
Sign up to set email alerts
|

Fetal development of the segment‐specific papillary body in the equine hoof

Abstract: Fetal development of the unique papillary body and its localized peculiarities in the equine hoof are described based on the study of 51 fetuses, nine newborn foals, and five adult horses. The shape and dimensions of the dermal papillae and lamellae have a formative influence on the structure and physical quality of the corneous hoof capsule with its horn tubules and lamellae. The size and arrangement of these horn structures determine the mechanical quality of hoof horn. Proper horn quality is a prerequisite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 16 publications
0
25
0
2
Order By: Relevance
“…Süsskind-Schwendi et al [4] reported the formation of claws in dogs. The skin and its appendages were studied in pigs by Meyer and Görgen [5], by Bragulla [6] in horses, by Bragulla et al [7] in cats and by Sengel [8] in mice. In general, this system has also been studied in mammals by Hardy [9] and in other vertebrates by OliveiraMartinez et al [10], who have focused on the molecular events that surround tissue differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Süsskind-Schwendi et al [4] reported the formation of claws in dogs. The skin and its appendages were studied in pigs by Meyer and Görgen [5], by Bragulla [6] in horses, by Bragulla et al [7] in cats and by Sengel [8] in mice. In general, this system has also been studied in mammals by Hardy [9] and in other vertebrates by OliveiraMartinez et al [10], who have focused on the molecular events that surround tissue differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos mostram ainda que fêmeas da espécie bovina com abscessos ou laminite tendem a diminuir a produção leiteira em comparação às sadias (Warnick et al 2001). Süsskind-Schwendi et al (2004) relatam o seu desenvolvimento em cães, Meyer & Görgen (1986) em suínos, Bragulla (2003) em equinos, Bragulla et al (2001) em felinos e Sengel & Mauger (1976) em camundongos. De maneira geral, esse sistema também foi estudado em mamíferos por Hardy (1992) e em alguns outros vertebrados por Oliveira-Martinez (2004) enfocando os eventos moleculares envolvidos na diferenciação dos tecidos.…”
Section: Introductionunclassified
“…Aufgrund der großen klinischen Relevanz von Huferkrankungen waren Struktur und Funktion des Hufes stets Gegenstand unterschiedlichster Untersuchungen sowohl in der Grundlagenforschung als auch in der angewandt-klinischen Forschung. Während insbesondere Hornstruktur und Hornbildung sowie biomechanische Eigenschaften des Zehenendorgans in den letzten Jahren im Zentrum des wissenschaftlichen Interesses standen (aktuelle Arbeiten über Anatomie und Biomechanik des Hufes : Pellmann 1995, Bragulla 1996, Henke 1997, Bowker et al 1998, Douglas et al 1998, Douglas und Thomasson 2000, Bragulla 2003, Egerbacher et al 2005, sind dagegen die Erkenntnisse zur Regulation der Mikrovaskularisation in diesem hoch spezialisierten Organ nach wie vor unvollständig und zum Teil widersprüchlich.…”
unclassified